Economics of bride-wealth-effect on sustainable marriage, a blessing or a curse? - The contemporary Southern Ghana context. (4th September 2019) - Amoah, Anthony; Okantey, Peter Carlos; Hughes, George; Fayorsey, Clara K.
In furtherance of the argument in literature, that a relationship exists between anthropology and economics because of the resource trade-off between families in the African marriage processes, we hypothesise that such payments ( bride-wealth ) may hurt the sustainability of marriage. Using a survey data obtained by administering a structured questionnaire to 247 respondents from Southern Ghana, we used the Tobit econometric technique to show that, some key determinants of bride-wealth in the study area include the bride's personal and family characteristics. In addition, using the ordinary least square, this study found that higher bride-wealth negatively affects the sustainability of marriages. Given that higher bride-wealth is found to hurt the sustainability of marriages, we recommend that a second look at payments of bride-wealth by cultures in Southern Ghana and other developing countries with similar characteristics must be considered. Thus, a call for a re-think of the payment of the high bride-wealth may be now!